CLUSTER ANALYSIS OF RISK PERCEPTION TO IMPLEMENT TOURIST HEALTH SAFETY IN VIETNAM - Ninh Van NGUYEN; Ngoc Thi Bich TRUONG (Geo Journal of Tourism and Geosites)
Perceived risk refers to tourists' objective assessment of the negative consequences associated with travel. The COVID-19 pandemic has significantly impacted all areas of human activity, influencing personal behavior and organizational practices. In post-COVID-19, travellers' perceptions of disease risk and behaviour have evolved. This study aimed to evaluate tourists' risk perceptions while travelling, categorizing them into distinct groups to identify differences among them. The research uses a mixed-method approach with validated surveys to measure travelers' risk perceptions via Likert scales. Data was collected from representative samples at destinations. K-means clustering identifies distinct segments, with the optimal number of clusters determined using the Elbow Method. Using cluster analysis, tourists were divided into three groups: Cluster 1 (32.18%), Cluster 2 (16.56%), and Cluster 3 (51.26%). The perceived risks were ranked in descending order as safety and hygiene risks, health risks, time risks, and emergency response support concerns. The analysis highlights that tourists prioritize safety, hygiene, health risks, and time risks when considering future travel, emphasizing the need for improved safety measures and effective tourism marketing strategies to restore traveler confidence. This study offers original insights through cluster analysis, showcasing the diverse risk perceptions among different social clusters and customer segmentation.